2016
DOI: 10.1038/nn.4274
|View full text |Cite
|
Sign up to set email alerts
|

Agouti-related peptide neural circuits mediate adaptive behaviors in the starved state

Abstract: In the face of starvation animals will engage in high-risk behaviors that would normally be considered maladaptive. Starving rodents for example will forage in areas that are more susceptible to predators and will also modulate aggressive behavior within a territory of limited or depleted nutrients. The neural basis of these adaptive behaviors likely involves circuits that link innate feeding, aggression, and fear. Hypothalamic AgRP neurons are critically important for driving feeding and project axons to brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
244
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(249 citation statements)
references
References 52 publications
5
244
0
Order By: Relevance
“…The onset of these currents was <3 ms after light delivery, which is within the time range of monosynaptic transmission (14). Furthermore, to identify which types of DMD neurons are synaptically connected to the vLPO Vgat neurons, we used the recording pipette to isolate mRNA from individual, light-responsive DMD neurons immediately after recordings and analyzed gene expression by single-cell reverse transcription PCR (RT-PCR) (15). These singlecell RT-PCR data showed that there were both Vgat + and Vglut2 Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…The onset of these currents was <3 ms after light delivery, which is within the time range of monosynaptic transmission (14). Furthermore, to identify which types of DMD neurons are synaptically connected to the vLPO Vgat neurons, we used the recording pipette to isolate mRNA from individual, light-responsive DMD neurons immediately after recordings and analyzed gene expression by single-cell reverse transcription PCR (RT-PCR) (15). These singlecell RT-PCR data showed that there were both Vgat + and Vglut2 Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…This finding contributes to a growing body of evidence related to the functional diversity of AgRP neurons. During periods of negative-energy balance activation of AgRP neurons not only provides a strong motivation to seek and consume food (45), but also helps to conserve energy by inhibiting energy-demanding physiological processes such as reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…This arrangement is observed in AgRP ‘hunger’ neurons 22 and in that case separate projections to distinct brain regions contribute to various aspects of hunger-related behaviors and physiology 3133 . CGRP PBN neurons project to the CeA and BNST 3,7 , nuclei that mediate behavioral and physiological responses to ingestive and fear-related stimuli 7,8,34 .…”
Section: Discussionmentioning
confidence: 88%
“…Inhibition from AgRP neurons or decreased input from anorexigenic neurons in the NTS 5 likely dampens CGRP PBN neuron activity during fasting 4 , but the decreases in calcium activity during food consumption are unlikely to come from AgRP neurons because they are inactive during feeding 22,36 . Because CGRP PBN neurons transmit potential danger signals, their inhibition during starvation might contribute to adaptive behaviors, such as increased risk taking to acquire food 31 , in addition to permitting increased food intake.…”
Section: Discussionmentioning
confidence: 99%